Effect of repeated applications of fipronil on arthropod populations in experimental plot studies - B. S., Ismail; A., Nuraziah; D., Nor Aini; A., Maimon (Universiti Putra Malaysia Press, 2004)
The effect of two applications of fipronil on arthropod populations were studied under experimental plot conditions using 3-month old Cuphea ignea. Eighty-one families belonging to 12 orders of Arthropoda were trapped before spraying. The four dominant orders were Hymenoptera (28.6%), Homoptera (19.1 %), Collembola (17.8 %) and Diptera (16.2 %). Other orders were present in small numbers i. e. Hemiptera, Coleoptera, Orthoptera, Thysanoptera, Araneida, Acarina, Lepidoptera and Isopoda. The abundance of arthropods was reduced to 44 and 47 families after the first and second sprayings, respectively. The percentage population of Collembola increased significantly after the first and second sprayings as compared to the number before treatment. The percentage population ofHomoptera (Aleyrodidae) increased after the first spray but declined after the second spray. The family Isotomidae (Collembola) increased significantly after the first and second sprays. Some orders such as Isopoda and Lepidoptera disappeared after the plot was treated with fipronil.